Acissitudes in the Shipping Trade, 1870-1920 - Gregg, E. S. (Quarterly Journal of Economics, 1921)
Vicissitudes in the Shipping Trade, 1870–1920 Get access E. S. Gregg E. S. Gregg New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 35, Issue 4, August 1921, Pages 603–617, https://doi.org/10.2307/1882428 Published: 01 August 1921